2021
DOI: 10.23925/2237-4418.2020v35i3p.87-109
|View full text |Cite
|
Sign up to set email alerts
|

Teletrabalho durante a pandemia

Abstract: Com a intensificação da necessidade de isolamento devido à pandemia gerada pela Covid-19, mudanças na forma de trabalhar foram impostas às organizações. Em meio a esse desafio, inúmeras organizações, públicas e privadas, passaram a praticar o teletrabalho ou intensificaram seus arranjos de trabalho flexíveis. Inclusive, o corpo técnico e docente das universidades. Nessa esteira, a presente pesquisa busca analisar a experiência de teletrabalho, durante a pandemia, da Universidade do Estado de Santa Catarina, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Brazilian teleworkers had highlighted performing domestic chores even before the pandemic (Filardi et al. , 2020) – and just continued in the Covid-19 scenario (Leite & Lemos, 2020; Pandini and dos Santos Pereira, 2020; PROGEP, 2020, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Brazilian teleworkers had highlighted performing domestic chores even before the pandemic (Filardi et al. , 2020) – and just continued in the Covid-19 scenario (Leite & Lemos, 2020; Pandini and dos Santos Pereira, 2020; PROGEP, 2020, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Filardi, Castro, and Zanini (2020) discovered perceptions of low WFC and higher interaction with the family, although domestic chores interfered with telework. During the pandemic, the studies reported: (1) women with varied perceptions about WFC, some mentioning work overload, some highlighting time gained for other activities (Lemos et al, 2021); (2) difficulties to reconcile different roles at home and how positive time flexibility was (Pandini and dos Santos Pereira, 2020); (3) WFC as one of the disadvantages, in addition to the distraction caused by household chores (Leite & Lemos, 2020).…”
Section: Telework Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…A different perspective highlights the importance of considering an individual's personal, family, social, economic, and psychological circumstances when analyzing telework. The productivity outcomes of this approach depend on these specific factors, leading to either positive or negative results (Latorre et al, 2021;Leite, 2020;Silva & Moraes, 2021). Additionally, the nature of the job performed by teleworkers plays a crucial role, as not all roles adapt equally well to remote work (Kawaguchi & Motegi, 2021).…”
Section: The Pandemic's Effects On Work and Workersmentioning
confidence: 99%